Studi Kasus: Penangan Masalah School refusal melalui Teknik Self Instruction pada Anak Sekolah Dasar - Rizki Ailulia; Aan Widiyono (Universitas Kanjuruhan Malang, 2021)
This study aims to find out how to overcome students' school refusal through self-instruction techniques. This study used four subjects in two public elementary schools in Tahunan District, Jepara Regency with different problem backgrounds. This research uses a case study design, with method steps including developing a conceptual model and research questions, treatment and documentation, presentation and case study reports, conclusions. Data collection techniques using interviews and observations with qualitative data analysis Miles and Hubermen. The results of this study found that the self-instruction technique was very effective in overcoming the problem of school refusal in children at SDN Tahunan District. The results of the treatment carried out by researchers have an influence on improving children's behavior in terms of controlling anger, improving discipline and compliance with school rules, independence in carrying out various activities, and being able to improve children's mental disorders.